Electoral behaviour in the Kraków metropolitan area: 1993-2011 - Linkowski, Radosław (Bulletin of Geography. Socio-economic Series, 2017)
The purpose of the paper is to describe changes in support for the four principal political options (’right’, ’left’, ’liberal’, ’peasant’) available in the Kraków Metropolitan Area (KMA) in parliamentary elections in the period 1993-2011. The electoral behaviour of the residents of the various KMA zones became increasingly similar in the study period. The political ’distance’ between the northern commuter zone of the KMA (part of the Russian partition in the 19th c.) and the rest of the KMA, decreased significantly. The suburban zone of Kraków also changed over the course of the study period by becoming significantly similar to the city in terms of voting behaviour. This political change was largely due to substantial social and economic changes in the rural parts of the metropolitan area. Urban areas in the KMA were much more stable in their voting patterns and tended to politically resemble one another much more than rural areas. The city of Kraków and the southern part of its commuter zone - part of the Austrian partition in the 19th c. - were characterized by fewer fluctuations in voting behaviour than the two remaining parts of the KMA.